Technology as an ally for the pleasant learning of students of the finance and banking management career of the Polytechnic University of Nicaragua (UPOLI) (Docentes 2.0 Journal, 2019)
At present, students comment that the techniques used by teachers are outdated but analyzing well; This is not far from reality, despite developing in a time of technological changes and innovations, there are still teachers who resist adapting to change.  However, there are teachers who have managed to form a progressive trend that bets on the improvement of learning environments and breaking the traditional paradigms, known as Pleasant Learning. This conception consists in creating an optimal environment for the educational process through a fresh and flexible amalgam of techniques, thus making it possible for students to achieve a true assimilation and appropriation of the knowledge transmitted by their teachers in a more enjoyable and friendly way.  A star ally of Pleasant Learning is Technology, formulating, creating and practicing innovative techniques, which can be developed in the classroom at any level of education. In the context of this paper, Technology has been used to develop Pleasant Learning for students of the Finance and Banking Management career of the Polytechnic University of Nicaragua, obtaining satisfactory results on the evaluations of the knowledge acquired and practiced.
Keywords: Technology; Pleasant Learning; UPOLI